PENERAPAN METODE EDUTAINMENT MELALUI PERMAINAN SIMAK-ULANG-UCAP UNTUK MENINGKATKAN KETERAMPILAN BERBICARA BAHASA ARAB - Karima, Karimna Isya (Departemen Pendidikan Bahasa Arab, 2019)
This research based on the first grade of MTs Ar-Rohmah’s students’ Arabic speaking skills. It was caused by the lack of application of in speaking Arabic. The students often feels bored and lack of confidence. So, the researcher was interested to find out differences in student’s speaking skill using Edutainment method. This study used quantitative approach, and quasi-experimental methodology. The techniques of collecting data are observation, interviews, test learning instruments, and documentation. The results are: (1) The mean value of experimental class’ pre-test has 41,25. Meanwhile in the control class has 51,40. (2) The mean value of experimental class’ post test has 63,43, meanwhile the control class has 59,68. (3) N-Gain Score’s test shows there was an increase in experimental class amounts 43.94% or 0,43 which in the average category. Besed on the results, the application of Edutainment method with ‘Listen-Repeat-Speak’ games can improve Arabic speaking skills.